2013
DOI: 10.1111/j.1600-6143.2012.04314.x
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus Replication and Nephropathy After Alemtuzumab-Induced Kidney Transplantation

Abstract: BK virus nephropathy (BKVN) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 20 publications
5
39
0
1
Order By: Relevance
“…68 This rate of BKV nephropathy did not differ significantly from that observed in patients who underwent less potent induction regimens with basiliximab, rATG, or steroids alone. 68 Previous studies of alemtuzumab induction and risk of BKV nephropathy have yielded both supporting and conflicting data.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…68 This rate of BKV nephropathy did not differ significantly from that observed in patients who underwent less potent induction regimens with basiliximab, rATG, or steroids alone. 68 Previous studies of alemtuzumab induction and risk of BKV nephropathy have yielded both supporting and conflicting data.…”
mentioning
confidence: 81%
“…68 This rate of BKV nephropathy did not differ significantly from that observed in patients who underwent less potent induction regimens with basiliximab, rATG, or steroids alone. 68 Previous studies of alemtuzumab induction and risk of BKV nephropathy have yielded both supporting and conflicting data. 29,[68][69][70][71][72][73][74] However, unlike most of the earlier studies, Theodoropoulos et al analyzed BKV nephropathy as a coprimary endpoint (along with onset of BK viruria or BK viremia), which strengthens the validity of their findings.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Of 2 prior studies that reported on late‐onset BKPyV, both defined “late‐onset” as BKPyV infection/disease that occurred after 6 months post‐transplant . This definition of “late‐onset” is problematic both because the mean/median onset of BKPyVAN is often later than 6 months and because all major guidelines recommend routine BKPyV screening up to 1 year post‐transplant. Recent studies have documented the histological evolution of BKPyVAN and have noted isolated late cases occurring >2 years post‐transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Cyclosporine is believed to be associated with a lower incidence of BKV nephropathy than tacrolimus, and mycophenolate mofetil is associated with a higher incidence of treatment for BKV compared with no antimetabolite therapy or azathioprine. 9,50-52 Whereas Retrospective cohort study 666 patients from January Induction with Alemtuzumab did not increase et al 49 2008 to August 2010 alemtuzumab vs the incidence of BK virus non-lymphocyte-depleting reactivation agents Abbreviations: BKVAN, BK virus-associated nephropathy; MMF, mycophenolate mofetil; OPTN, Organ Procurement and Transplantation Network; SRTR, Scientific Registry of Transplant Recipients data on mammalian target of rapamycin inhibitors, sirolimus and everolimus, are limited, it would be safe to state that they are not associated with an increased risk of BKV nephropathy. 50,[53][54][55] It is well established that the combination of tacrolimus and mycophenolate mofetil is associated with a significantly higher risk for BKV nephropathy 56,57 ( Table 1).…”
Section: Risk F Actorsmentioning
confidence: 99%